Ultra Performance Liquid Chromatography Assay for Cinnarizine in Lipid-Based Formulations - Abdel-Hamid, M.; Shahba, A.; Mohsin, K.; Alanazi, F. (Asian Journal of Chemistry, 2011)
The objective of present study is to evaluate UV-VIS spectrophotometry and ultra performance liquid chromatography (UPLC) methods for quantification of cinnarizine in lipid-based formulations. The direct spectrophotometric method was carried out at 253 nm, which gave good linearity (R2 = 0.999), but was unsuitable for cinnarizine quantification within lipid-based formulation due to significant matrix interference. While the ultra performance liquid chromatography reversed phase method was composed of isocratic mobile phase, 0.25 % trifluoroacetic acid in 50 % acetonitrile with flow rate 0.5 mL/min, column BEH C18 (2.1 × 50 mm, 1.7 μm) found to be rapid (1min run), selective with well resoluted cinnarizine peak from different lipid matrices and degradation product (resolution >2.0) and sensitive (LOD = 0.1ppm and LLOQ = 0.5ppm) at 251 nm. The accuracy and precision were within the standard FDA limits. The study suggests that the developed ultra performance liquid chromatography method can be used for the assessment of drug purity, stability, lipid-formulation release profile and dissolution rate without any interference of excipients and/or degradation products.